Demography and spatial distribution of a threatened species from the Atlantic Forest in southern Brazil: differences between urban and rural remnants - Pinto, M. B. (2023)
Logging and agricultural exploitation have led to the degradation of Araucaria Forest remnants and the alteration of its last preserved patches. This forest typology contains many endangered plant species, as is the case of the tree Oreopanax fulvus Marchal. To support conservation of this species and understand how different landscape matrices can influence its populations, we evaluated the demographic structure and spatial distribution of O. fulvus in two Araucaria Forest remnants in Paraná state. We delimited two plots (urban and rural population), each with 1 ha, subdivided them into 100 subplots (10 x 10 m), and recorded diameter at ground level (DGL), height, and coordinates of two post-germinative developmental stage of individuals. In each subplot, we measured slope, luminosity, and canopy height. We used Ripley’s K function analysis to describe distribution patterns of the species and the spatial relationship between mature and juvenile trees. We performed correlations between abundance and environmental and structural variables of the O. fulvus populations. Abundance varied between remnants, from 183 individuals/ha (12 mature and 171 juvenile) to 1306 individuals/ha (10 and 1296). The remnants varied in abundance and plant frequency. The species showed an investment in seedling banks. Most juvenile had DGL up to 3.0 cm and height up to 1.0 m and presented aggregated spatial distribution, while adults had random distribution. In the rural population juvenile abundance were correlated with canopy height (positively) and distance to mature trees (negatively). The slope was correlated for both sites, but oppositely, indicating that other factors might have interfered in the regeneration abundance. The urban remnant showed a high abundance of this endangered species, calling attention for potential studies in urban arborization, management and conservation of these remnants.